Stable curcumin-loaded polymeric micellar formulation for enhancing cellular uptake and cytotoxicity to FLT3 overexpressing EoL-1 leukemic cells - Singkome Tima (2018)
ï¿½ 2017 Elsevier B.V. The present study aims to develop a stable polymeric micellar formulation of curcumin (CM) with improved solubility and stability, and that is suitable for clinical applications in leukemia patients. CM-loaded polymeric micelles (CM-micelles) were prepared using poloxamers. The chemical structure of the polymers influenced micellar properties. The best formulation of CM-micelles, namely CM-P407, was obtained from poloxamer 407 at drug to polymer ratio of 1:30 and rehydrated with phosphate buffer solution pH 7.4. CM-P407 exhibited the smallest size of 30.3 ï¿½ 1.3 nm and highest entrapment efficiency of 88.4 ï¿½ 4.1%. When stored at −80 ï¿½C for 60 days, CM-P407 retained high protection of CM and had no significant size change. In comparison with CM solution in dimethyl sulfoxide (CM-DMSO), CM kinetic degradation in both formulations followed a pseudo-first-order reaction, but the half-life of CM in CM-P407 was approx. 200 times longer than in CM-DMSO. Regarding the activity against FLT3 overexpressing EoL-1 leukemic cells, CM-P407 showed higher cytotoxicity than CM-DMSO. Moreover, intracellular uptake to leukemic cells of CM-P407 was 2–3 times greater than that of CM-DMSO. These promising results for CM-P407 will be further investigated in rodents and in clinical studies for leukemia treatment.